CTA's Data4Ag Experiences - Addison, Chris (Technical Centre for Agricultural and Rural Cooperation, 2019)
Chris Addison, Senior Programme Coordinator at CTA, shares the Centre s work on data for agriculture with various farmer organisations, and the results achieved so far.